Effect of surgical mandibular setback on the occurrence of obstructive sleep apnea - Thanyaphat Engboonmeskul; Narit Leepong; Premthip Chalidapongse (Journal of Oral Biology and Craniofacial Research)
The aims were to assess the airway morphologic changes, and to evaluate sleep respiratory function and the occurrence of obstructive sleep apnea (OSA) after mandibular setback. Fifteen prognathism patients underwent bilateral sagittal split ramus (BSSRO) with or without maxilla surgery were grouped by distance of mandibular setback as group A (≤6 mm, n = 7) and group B (>6 mm, n = 8). Morphological changes were assessed using lateral cephalometric radiography and cone-beam computed tomography (CBCT) at preoperative (T0) and 6 months after surgery (T1). Sleep respiratory functions were evaluated using polysomonography. On lateral cephalometric radiography, group B showed significant decreased at Vp (p = 0.028) and PAS-p (p = 0.017). It also significant different between groups (p = 0.011 and p = 0.009 respectively). On CBCT, airway volume and AP width of airway, except Np, decreased in both groups but not significant different between groups. Only group A showed significant different between T0 and T1, cross-sectional area of Vp (p = 0.043), AP width of Vp (p = 0.043), Hp (p = 0.042), and PAS-t (p = 0.043). In group B, apnea hypopnea index increased at T1 (p = 0.043) and REM sleep differed between groups (p = 0.04). In conclusion, mandibular setback decreased the pharyngeal airway dimensions although no OSA occurred. It might be predisposing of OSA.